2010
DOI: 10.1620/tjem.222.237
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Bronchiectasis in Adults: Analysis of CT Findings in a Health Screening Program

Abstract: Bronchiectasis is one of the common chronic respiratory diseases and associated with respiratory morbidity and mortality. However, neither its prevalence nor its etiology is well-defined. We aimed to estimate the prevalence and risk factors of bronchiectasis in adults. In a retrospective study, we analyzed radiologic findings on chest computed tomography (CT) images performed as part of a health-screening program. From January to December 2008, 1,409 (24.6%) of 5,727 participants in the screening program of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 25 publications
(41 reference statements)
6
51
1
3
Order By: Relevance
“…In agreement with the later study by Seitz and co-workers, our average annual age-adjusted hospitalization rate for bronchiectasis as the primary diagnosis was 1.8 per 100,000 population, with an increasing trend that was most pronounced among females with bronchiectasis as the primary diagnosis [8]. Hospitalization rates were generally higher among aged subjects, as reported previously [2], [5], [6], [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the later study by Seitz and co-workers, our average annual age-adjusted hospitalization rate for bronchiectasis as the primary diagnosis was 1.8 per 100,000 population, with an increasing trend that was most pronounced among females with bronchiectasis as the primary diagnosis [8]. Hospitalization rates were generally higher among aged subjects, as reported previously [2], [5], [6], [8].…”
Section: Discussionsupporting
confidence: 92%
“…Between 2005 and 2011, on average 48% of the total male, but only 43% of the total female German population aged ≥65 years (and 60% vs. 54% among those aged ≥75 years) had been hospitalized (data not shown), despite a clear predominance of females in this subpopulation [15]. This suggests that, although the most pronounced increases of hospitalization rates were observed among females, bronchiectasis may still be underdiagnosed among the more advanced age groups in Germany, particularly among elderly women [6]. On the one hand, this argues against more severe disease and frequent readmissions among the more advanced age groups.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may partly explain the disparities found in the reported prevalence. Moreover, most of these studies excluded patients with previously known bronchiectasis and those with bronchiectasis in only one pulmonary segment, as this circumstance can be found in a significant percentage of elderly people in the general population, or in smokers with no airway obstruction 29. Recently, Tan et al30 found that 19.9% of healthy individuals had bronchiectasis compared with 35.1% of severe COPD patients of the same age.…”
Section: Prevalence Of Bronchiectasis In Copdmentioning
confidence: 99%
“…[6,29,30] A population survey in China (n = 66,546) [31] demonstrated that the prevalence of tuberculosis infection was about 44.5% (29,557/66,546) when a positive response to purified protein derivative (PPD)-RT23 (≥6 mm) was used as the diagnostic criterion. More recently, a prospective cohort study of rural residents in China (n = 21,022) [32] showed that the rate of latent tuberculosis infection, determined by a positive result of IFN-γ release assay, was 19%.…”
Section: Discussionmentioning
confidence: 99%